Políticas públicas de turismo na Ilha do Marajó: turismo e apropriação da paisagem no município de Soure - Pará - SANTANA, Eliane de Jesus Miranda (Universidade Federal do Pará, 2014)
Soure municipality Marajó Island has great tourism potential, particularlt for its natural landscapes, like beaches and farms, before this and for being one of the towns closest to the Marajó state capital, became one of the most visited by tourists, among other facts that led the city to receive marajoara state intervention through public policies aimed at promoting tourism in the state of Pará the present study aims to analyze the public policies of tourism, in which is inserted Soure. However, the focus of this review is about the appropriation of the landscape by the State, through these actions that seeks to promote tourism in the city since the 1970s. We tried to analyze the appropriation of the landscape by the state, market, tourists and locals as well as the last three are included in those policies. The study was conducted based on the geographical analysis of tourism, because tourism means, beyond the economic bias, as a socio activity. To achieve the objectives followed by the following methodological steps: collection, organization and systematization of the information contained in the documents. Fieldwork, where interviews were conducted with tourists and locals. Anyway, it was observed that the landscape of Soure is used in policy on the perspective of exoticity, a characteristic that is also used by the tourist trade, but the local population, not contradictory in its entirety enjoy the landscape of the city. There is a process in Soure touristification, actually provided by the state, tourism industry and tourists, while the local population secondary role in this process.